Estimulação elétrica neuromuscular em cães submetidos à imobilização rígida, temporária da articulação femoro-tíbiopatelar - Souza, Soraia Figueiredo de (2006)
The objective of this study was to evaluate the effects of neuromuscular electrical stimulation (NMES) of low frequency on the vastus lateralis muscle. Eleven, male and female, dogs of variable age were randomly placed in 3 groups: I (control), II (NMES post immobilization), and III (NMES before and post immobilization). The right femoral-tibial-patellar joint of the animals in groups I, II, and III was immobilized for 30 days by the percutaneous transfixation type II method. The dogs from group II were placed on eletrotherapy 3 times weekly for 90 days, during (30 days) and post immobilization (60 days). The dogs from group II were initiated on NMES post-removal of the temporary rigid immobilization. The parameters evaluated consisted of: measurement of thigh circumference, joint motion using a goniometer, gait analysis, creatine kinase (CK) and aspartate aminotransferase (AST) levels and morphometry of the longitudinal muscle fibers collected by vastus lateralis muscle biopsy. The gait analysis was performed daily by the same observer for 90 days. The circumference of the thigh, joint motion, and muscle biopsy were performed on days 0, 30, 60 and 90 post-surgery. The blood samples for CK and AST were collected before and immediately after 6, 24 and 48 hours post-NMES on days 0,1,7,30,45,60,75 and 90. The NMES was employed on the femoral quadriceps muscle group with a frequency of 50Hz post-duration of 300msec on an off-time/on-time ratio of 1:2. There was no significant difference on the gait analysis, thigh circumference, joint motion, and CK and AST values. In terms of morphometry of muscle fibers, the greatest hypertrophy change was observed on longitudinal fibers of the dogs from group II (p=0.0005), followed by the dogs from group III. It can be concluded that NMES of low frequency does not avoid the muscular atrophy of vastus lateralis muscle during rigid temporary immobilization of the stifle joint, but causes muscular gain after this period, recommending its use